A ball of clay. - Hawkinson, John, 1912- (Chicago, A. Whitman, 1974)
Introduces clay as an art medium with information on how to find it in nature, prepare it for handling, and use it to create a variety of non-permanent projects.
10 13
Keywords: Clay modeling; Modeling -- Juvenile literature